Interdisciplinary Integration among Clinical Pharmacists, Medical Technologists, Patient Care Technicians, and CSSD Technicians: A Conceptual Framework for Enhancing Patient Safety and Healthcare Quality - Sarah Mansour Almuawi, Thekra Salem Al Hthloul, Ali Yahya Asiri, Hamoud Alharbi, Eman Mohammed Alfi, Raffah Mahdi Bajudah, Raghad Saleh Alshehri, Aljawharah Saed Salem Aldawsari, Saleh Khalaf Alqulib, Faisal Alasmari, Khalid Mohammed Alhudaib, Sultan Yahya Almalki, Amal Yahya Sanah, Asma Saeed Ahmed Badawood (Journal of Daoist Studies, 2026)
This study aimed to develop a conceptual framework for enhancing patient safety and healthcare quality through interdisciplinary integration among Clinical Pharmacists, Medical Technologists, Patient Care Technicians (PCTs), and Central Sterile Services Department (CSSD) Technicians. The increasing complexity of healthcare systems has highlighted the need for effective collaboration among healthcare professionals to reduce preventable errors, improve communication, and strengthen quality of care. A descriptive cross-sectional research design was employed to explore the current status of interdisciplinary integration within healthcare institutions. The study was conducted in three tertiary healthcare hospitals that provide comprehensive medical, pharmaceutical, laboratory, and sterilization services. The target population consisted of 420 healthcare professionals, including Clinical Pharmacists, Medical Technologists, Patient Care Technicians, and CSSD Technicians, from which a representative sample of 301 participants was selected using a stratified sampling technique. Data were collected through a structured questionnaire developed from an extensive review of the literature on patient safety, healthcare quality, teamwork, and interprofessional collaboration. The findings demonstrated that effective interdisciplinary integration is supported by four major domains: communication, collaboration, patient safety, and healthcare quality. Clinical Pharmacists contributed primarily to medication safety and therapeutic optimization, Medical Technologists supported diagnostic accuracy and laboratory quality, Patient Care Technicians enhanced patient monitoring and continuity of care, while CSSD Technicians played a vital role in infection prevention and sterilization management. The results indicated that coordinated communication, shared responsibilities, and mutual professional support strengthen healthcare performance and contribute to safer patient outcomes. Based on these findings, a conceptual framework was developed to facilitate interdisciplinary collaboration and improve healthcare quality. The study concludes that integrating the expertise of these professional groups can significantly enhance patient safety, reduce healthcare risks, and support continuous quality improvement within healthcare organizations.